Determinants of HIV provider-initiated testing and counseling screening service used by pregnant women in primary health centers in Surabaya (Faculty of Medicine Universitas Indonesia, 2017)
Background: Offering free HIV screening service for pregnant women in primary health center in Surabaya has become obligatory since 2014, but only 70% used the service. Prior studies on HIV screening mostly focused on Voluntary Counseling and Testing. Methods: This was a cross-sectional study. Interviews were conducted with 150 pregnant women attending antenatal care in 1 of 9 public health centers (PHCs) in Surabaya and offered HIV screening within the same PHC. The eligibility criterium was pregnant women attending antenatal care in PHCs. The exclusion criteria were having been counseled for HIV prior to the interviews and/or experiencing an obstetric emergency. Using PRECEDE Framework with the concept of a comprehensive framework, this study focuses on identifying determinants of HIV PITC service use in PHCs in Surabaya. Binary logistic regressions and multiple binary logistic regressions were used in analyses. Results: The service use was associated with self-confidence of getting blood drawn for the test (p<0.001, adjusted OR=12.368, 95% CI=3.237–47.250) and past use of midwife private service for current pregnancy (p=0.029, adjusted OR=3.902, 95% CI=1.150–13.246). Self-confidence of getting blood drawn for HIV test mediated the effect of past use of midwife's private service on HIV screening use. Conclusion: Past use of midwife's private service affected self-confidence of getting blood drawn for HIV test on HIV screening use, and self-confidence affected the use of HIV PITC. This study results suggest that more midwives' private practices are needed to increase the use of HIV PITC screening in PHC.